Analisis Potensi Kekeringan Meteorologis di Daerah Aliran Sungai (DAS) Ciliwung (Analysis of Meteorological Drought Potential in The Ciliwung River Basin) - Dyah Rizky Alyudin; Amanah Anggun Prambandari; Nur Azizah; Kurnia Anggraini; Tito Latif Indra (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2024)
The Ciliwung River and the Ciliwung River Basin play an important role in the availability of water in the river basin and its surrounding areas. However, the sustainability of water availability in the Ciliwung River Basinrequires attention to threats such as drought. Research on the potential for drought is one step in anticipating water availability in the Ciliwung River Basinand its surrounding areas. Meteorological drought is a form of drought that can be detected through simple steps using rainfall data as the main data. With rainfall data, drought potential analysis can be carried out using 3-monthly SPI calculations, and statistical analysis of rainfall and its relationship to meteorological phenomena closely related to drought such as ENSO. Statistical analysis and SPI show that almost all observation points have indications of drought, namely Cibereum Bogor, Citeko, Gadog, Pinangsia, Ancol Pump, North Sunter Reservoir, Cempaka Baru, Bukit Duri, Manggarai and Kemayoran. In Katulampa, there are different analysis results, withstatistical analysis showings a decreasing trend in rainfall while the SPI results show normal values. This shows that overall statistical analysis and SPI can support each other. Almost all areas of the Ciliwung River Basinshow SPI values ​​in the normal to dry category for October 2023 and increasingly dry in several points from November to December 2023, which are in Citeko, Depok, Cibereum, Gadog, Manggarai, and Kemayoran. However, SPI and statistical analysis have weaknesses, namely its dependence on the amount of rainfall observation data available.